THU0047 Resveratrol and its precursor polydatin inhibit crystal-induced inflammation in vitro by decreasing oxidative stress and il-1beta activation pathway. (15th June 2017) - Zamudio-Cuevas, Y; Oliviero, F; Belluzzi, E; Scanu, A; Andretto, L; Galozzi, P; Favero, M; Ramonda, R; Spinella, P; Ravagnan, G; Lopez-Reyes, A; Punzi, L
Abstract : Background: Resveratol (RES) and its natural precursor polydatin (PD) are polyphenol compounds that display a broad variety of beneficial effects including anti-apoptotic and anti-inflammatory properties. Objectives: This study aimed to investigate the role of RES and PD in the inflammatory process induced by monosodium urate (MSU) and calcium pyrophosphate (CPP) crystals in vitro. Their effect was evaluated though IL-1β, NLRP3 inflammasome, reactive oxygen species (ROS), nitric oxide (NO) and the phagocytosis index assessment. Methods: A monocytic cell line (THP-1) was primed for 3 hours with phorbol myristate acetate (PMA) (100ng/ml) and stimulated with synthetic MSU (0.05mg/ml) and CPP (0.025mg/ml) crystals. RES and PD were added to cultures at, respectively, 100μM and 200μM. Experiments were carried out either adding RES and PD along with crystals, or pretreating cells (2 hs) with polyphenols and removing them before crystal stimulation. IL-1β were evaluated in cell supernatants and at intracellular level by ELISA assay. IL-1β and NLRP3 expression was assessed by RT-PCR. Reactive oxygen species (ROS) and NO were measured by cytometric analysis using fluorogenic probes (CellROX Deep Red Reagent and DAF-FM, respectively). Crystal phagocytosis index was calculated at different time points using polarized light microscopy. Results: RES and PD inhibited IL-1b induced by crystals both at extracellular and intracellular level. This inhibition was more pronounced after polyphenol cell pretreatment. In this case cytokine production was completely suppressed both in control and in stimulated cells. Cell pretreatment was extremely effective also in reducing mRNA expression of IL-1 after crystal stimulation while NLRP3 expression was to some extent affected by RES. RES and PD had a slight inhibitory effect on crystal phagocytosis when added along with the stimulus, while pretreated cells did not show any difference in the phagocytosis index. ROS production induced by MSU crystals was more pronounced (4 fold increase) with respect to CPP crystals (2 fold increase). RES was more effective than PD in inhibiting ROS production (p<0.05 crystals vs crystals+RES). The pretreatment showed a more marked decrease of ROS than the simultaneous treatment and the effect reached significance for both PD and RES. Similar inhibitory effects have been obtained when NO production was considered. Conclusions: Our results demonstrated that RES and PD are effective in inhibiting crystal-induced inflammation affecting IL-1 production and NLRP3 expression and activation. Data obtained after cell pretreatment allow us to hypothesize that these polyphenols act on specific signaling pathway preventing inflammation, and that this action is independent from crystal phagocytosis. Disclosure of Interest: None declared